Experimental study of transcranial pulsed current stimulation on relieving athlete’s mental fatigue - Shen, Yangyang; Liu, Jian; Zhang, Xinming; Wu, Qingchang; Lou, Hu (Frontiers in Psychology, 2022)
Objective: To explore the effect of independently developed transcranial pulsed current stimulation (tPCS) on alleviating athlete’s mental fatigue. Methods: A total of 60 college athletes were randomly divided into active stimulation group (current intensity:1.5 mA, lasting for 15 min) and sham stimulation group. Subjective questionnaires, behavior test and fNIRS test were conducted before and after the experiment. Two-way ANOVA with repeated measures was used to compare the differences of mental fatigue indexes before and after the two experimental conditions. Results: After 7 days of exercise training, there was a significant difference in the main effect of time factor in all indexes of the two groups (p < 0. 05). The scores of rated perceived exertion (RPE) scale, positive and negative affect schedule (PANAS), RESTQ76-Sport Questionnaire, critical flicker frequency (CFF), reaction time (RT), oxyhemoglobin (HbO2), deoxyhemoglobin (HHb), total hemoglobin (HbTot) and hemoglobin difference (HbDiff) in the tPCS treatment group were better than those in the sham stimulation group (p < 0. 05). After 7 days of exercise training, all the subjects had different degrees of athlete’s mental fatigue; the subjects in the active stimulation group have a good evaluation of the tPCS developed by the research group without adverse actions. Conclusions: tPCS intervention can improve emotional state, reduce subjective evaluation of fatigue, improve behavioral levels such as attention and reaction time and increase cerebral prefrontal blood flow and oxygen supply.